Economic distress and perceptions of sexual intimacy in remarriage - Turner, Joshua J.; Crapo, J. Scott; Kopystynska, Olena; Bradford, Kay; Higginbotham, Brian J. (Frontiers in Psychology, 2023)
Introduction Economic distress and the relationship stability of remarried couples has been subject to some exploration, but less emphasis has been placed on how economic distress among remarried couples impacts other relationship domains, particularly sexual intimacy. Methods Through the lens of multidimensional family development theory (MFDT), this study utilizes longitudinal data over a three-year period to examine the links between economic distress, couple engagement, relationship satisfaction, and perceptions of sexual intimacy among remarried couples (n = 1,161 couples; 97% White). Results Through a dyadic structural equation model, results showed that wives’ report of economic distress was directly related to their self-rejection of a partner’s sexual advances. Findings also revealed gender differences in how both relationship satisfaction and couple engagement influenced one to accept or reject their partner’s sexual advances, with couple engagement acting as a significant predictor for wives. Relationship satisfaction was also found to explain (i.e., mediate) the relation between economic distress and sexual intimacy, but only for husbands. Discussion Implications for further research and interventions designed to strengthen the relationships of remarried couples dealing with economic distress and intimacy issues are offered.